A Conceptual Model of the ICT Support for Intellectual Capital Management - Olszak, Celina M.; Ziemba, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The article aims at presenting how to apply information technologies to support intellectual capital management. At the very beginning intellectual capital and its management are both characterised. Then application of information systems and technologies is shown in the context of intellectual capital sources and objectives of intellectual capital management. The final part of the article focuses on the role of corporate portals in intellectual capital management.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 89-101